2021
DOI: 10.48550/arxiv.2102.02357
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Speed of sound in dense matter and two families of compact stars

Silvia Traversi,
Prasanta Char,
Giuseppe Pagliara
et al.

Abstract: We investigate the possibility of having massive compact stars, (M > 2M ), and at the same time fulfilling the theoretical bounds on the speed of sound cs in dense matter suggesting that the conformal limit of c 2 s = 1/3 is approached from below as the density increases. This is possible if two families of stars exist: hadronic stars and quark stars, the latter being entirely composed by quark matter. By using astrophysical data on electromagnetic and gravitational waves signals of a few sources interpreted a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…The allowed maximum mass of nonstrange stars is larger than the strange ones, up to ∼ 2.7 M for an extremely low surface density close to the nuclear saturation density ρ 0 . The hypothetic absolute stability of quark matter, allowed by an ample parameter space in the present model calculations, not only theoretically supports quark stars as viable alternative physical model for neutron stars [32,70,[92][93][94][95][96][97][98], but also could have important consequences on various astrophysics and cosmological problems, such as supernovae [99][100][101], gamma-ray bursts [102][103][104][105][106][107], fast radio bursts [108][109][110], pulsar glitch [111,112], cosmic rays [113]. In future work, we plan to include the diquark channels for quark superfluidity for improving the phenomenological models of strong interactions at finite density, to advance the understanding of quark matter and make an attempt to tackle the unresolved questions in connection with it.…”
Section: Conclusion and Summarymentioning
confidence: 60%
“…The allowed maximum mass of nonstrange stars is larger than the strange ones, up to ∼ 2.7 M for an extremely low surface density close to the nuclear saturation density ρ 0 . The hypothetic absolute stability of quark matter, allowed by an ample parameter space in the present model calculations, not only theoretically supports quark stars as viable alternative physical model for neutron stars [32,70,[92][93][94][95][96][97][98], but also could have important consequences on various astrophysics and cosmological problems, such as supernovae [99][100][101], gamma-ray bursts [102][103][104][105][106][107], fast radio bursts [108][109][110], pulsar glitch [111,112], cosmic rays [113]. In future work, we plan to include the diquark channels for quark superfluidity for improving the phenomenological models of strong interactions at finite density, to advance the understanding of quark matter and make an attempt to tackle the unresolved questions in connection with it.…”
Section: Conclusion and Summarymentioning
confidence: 60%
“…Considerable efforts are undertaken in the literature to pursue the underlying mechanism explaining the rapid growth in c s (McLerran & Reddy 2019). However, from our present study of SQSs with a bag-modellike EOS, it is found that c s is essentially a constant close to c/ √ 3 (see also in Traversi & Char 2020;Traversi et al 2021)); A heavy compact star does not necessarily demand a superconformal c s as long as the EOS stiffening happens early. In fact, we generally have two kinds of EOSs in our model: The first kind has the maximum sound speed at a low density corresponding to the zero pressure point, while the second kind reaches its maximum c/ √ 3 at asymptotic density.…”
Section: Sound Speed In Dense Mattermentioning
confidence: 65%
“…One key point is still unclear, i.e., whether compact stars are gravity-bound neutron stars (NSs) or indeed self-bound quark stars (QSs)? After decades of speculation (Bodmer 1971;Witten 1984), QSs still serve as viable alternative physical model for compact Corresponding author: Ang Li liang@xmu.edu.cn stars (Baym et al 1985;Glendenning 1990;Weber 2005;Li et al 2016;Zhou et al 2018;Bombaci et al 2021;Cao et al 2020;Traversi et al 2021;Sedaghat et al 2021).…”
Section: Introductionmentioning
confidence: 99%